Importance of Skills Development for Ensuring Graduates Employability: The Case of Bangladesh - Md Jahangir Alam; Keiichi Ogawa; Sheikh Rashid Bin Islam (Social Sciences, 2022)
Graduate employability is a multifaceted concept considering the Sustainable Development Goals. Graduate employability and skills development are also significant determinants for future career success. Graduate employability has seen more sweeping emphasis and concerns in national and global job markets, due to the ever-rising number of unemployed people, which has increased even more due to COVID-19. Due to its importance, this study investigates the current state of skill development initiatives in Bangladesh and the perceptions of university graduates regarding skill development for their future employability. This study uses mixed-method research. Data was collected through surveys and in-depth interviews; various probabilistic and non-probabilistic sample selection methods were used. A total of 437 participants responded to this study. After analysis, the data was shown descriptively. The empirical findings of this study demonstrated that university graduates are well-aware of the skill development requirements for their future employability. However, university graduates face many obstacles in acquiring these necessary skill development opportunities. Therefore, the government and relevant stakeholders must work together to alleviate the obstacles. Furthermore, this study includes recommendations that can assist in developing a model for skill development programs and initiatives in the country for university graduates to ensure their future employability.